1997
DOI: 10.1002/(sici)1097-0347(199703)19:2<137::aid-hed9>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the larynx after resection of a carcinoma of the posterior wall of the hypopharynx: Versatility of a free flap patch graft

Abstract: Background Preservation of the larynx after resection of a pharyngeal tumor remains a challenging problem for the head and neck surgeon. Methods Nine patients with T1 or T2 carcinoma of the posterior wall of the hypopharynx (UICC 1987), who were treated surgically between 1984 and 1994, were studied. All patients underwent surgical resection of the tumor with laryngeal preservation and immediate reconstruction with free flap transfer. A free forearm flap was transferred in four patients and a free jejunal patc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 17 publications
0
17
1
Order By: Relevance
“…Regarding swallowing rehabilitation, results were similar between these two flaps, with a median time for removal of the feeding tube of 1 month in both groups. We do not have experience in reconstruction with a jejunal free flap patch graft, as described by Nakatsuka et al, 11 because we worried about mucous secretion and aspiration problems. This author did not experience such problems on the four patients in his study, but the results need to be confirmed with a larger series.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding swallowing rehabilitation, results were similar between these two flaps, with a median time for removal of the feeding tube of 1 month in both groups. We do not have experience in reconstruction with a jejunal free flap patch graft, as described by Nakatsuka et al, 11 because we worried about mucous secretion and aspiration problems. This author did not experience such problems on the four patients in his study, but the results need to be confirmed with a larger series.…”
Section: Discussionmentioning
confidence: 99%
“…After consecutive intensive treatment and swallowing therapy, the patient started swallowing without aspiration 2.5-3 months after surgery. According to the international literature [25][26][27][28] swallowing can be achieved in such cases with hypopharyngectomy within 3-4 months, especially if there is a postoperative massive swelling, which is primarily resistant to medical therapy. Radical oncological surgical resection is the therapy of choice in cases of carcinoma in a Zenker's diverticulum.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction of portions of the tongue or supraglottis is critical in order to obtain good functional results. Radial forearm flaps have been used successfully for larynx preservation in reconstructing the posterior wall of the hypopharynx [7,9]. Because of its versatility, this free flap can also be used to reconstruct laryngeal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Since shrinkage of a flap may occur, especially after irradiation, the size of the free flap should be at least 10% larger than the area to which it will be grafted [7]. Because of the need for bulky reconstruction, the dimensions should be increased even more to ensure good larynx protection.…”
Section: Discussionmentioning
confidence: 99%